Students’ Engagement in AI-Supported English Language Learning: A Qualitative Case Study of Senior High School Students in Palopo City - Andi Mangnguntungi Sudirman; Sri Rahayu; Hermini Hermini (Education and Talent Development Center Indonesia (ETDC Indonesia), 2026)
Artificial intelligence (AI) is increasingly used in English as a foreign language (EFL) classrooms to provide immediate feedback, personalized assistance, and interactive learning. However, evidence of its impact on students’ engagement, particularly in Indonesian senior high schools, remains limited. This qualitative case study explored students’ behavioral, emotional, and cognitive engagement during AI-mediated English learning in Palopo City. The study provides practical insights into integrating AI into classroom instruction while maintaining the teacher’s pedagogical role. Data were collected through four classroom observations involving 30 eleventh-grade students, semi-structured interviews with one English teacher and eight purposively selected students, and supporting documentation. The data were analyzed using thematic analysis. The findings indicate that AI supported engagement across three interrelated dimensions. Behavioral engagement was most evident, as students paid greater attention, responded more quickly, and participated more actively in classroom activities. Emotional engagement was reflected in students’ enjoyment, confidence, excitement, and pride as they received feedback and recognized their learning progress. Cognitive engagement emerged when students compared responses, reflected on mistakes, reconsidered their understanding, and discussed alternative answers with peers. Nevertheless, AI implementation also presented challenges, including pressure from task pace, overreliance on AI-generated responses, unstable internet access, and unequal device availability. The study concludes that AI can strengthen behavioral, emotional, and cognitive engagement in EFL learning when used as a pedagogical tool supported by clear instructional objectives and active teacher guidance. Effective integration requires structured reflection, responsible AI use, and classroom practices that encourage students to think critically beyond AI-generated responses.